2015
DOI: 10.1002/ase.1553
|View full text |Cite
|
Sign up to set email alerts
|

Who is repeating anatomy? Trends in an undergraduate anatomy course

Abstract: Anatomy courses frequently serve as prerequisites or requirements for health sciences programs. Due to the challenging nature of anatomy, each semester there are students remediating the course (enrolled in the course for a second time), attempting to earn a grade competitive for admissions into a program of study. In this retrospective study, remediation rates and trends in an undergraduate anatomy course with over 400 students enrolled each semester at a large Midwestern university were identified. Demograph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 35 publications
0
32
1
Order By: Relevance
“…There are multiple reasons why human anatomy courses may be difficult for allied health students. They have been identified as academically challenging due to the amount and complexity of content; a source of emotional stress for students; and commonly situated in the first year of their program when the student may be already struggling to adapt to the requirements of university education (Hancock et al, ; Whittle and Bickerdike, ; Bruno et al, ; Schutte, ). The provision of supplementary instructional videos did not improve the learning or anatomy self‐efficacy of the whole cohort.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are multiple reasons why human anatomy courses may be difficult for allied health students. They have been identified as academically challenging due to the amount and complexity of content; a source of emotional stress for students; and commonly situated in the first year of their program when the student may be already struggling to adapt to the requirements of university education (Hancock et al, ; Whittle and Bickerdike, ; Bruno et al, ; Schutte, ). The provision of supplementary instructional videos did not improve the learning or anatomy self‐efficacy of the whole cohort.…”
Section: Discussionmentioning
confidence: 99%
“…A sound knowledge of human anatomy is vital for many allied health professions and consequently a requirement in allied health undergraduate programs. Human anatomy courses have been identified as challenging and high‐risk for elevated attrition and failure rates (Bruno et al, ; Schutte, ). Multiple contributing factors have been suggested—the high intrinsic cognitive load associated with the terminology, large volume of information, and complexity of material (Leppink and van den Heuvel, ) combined with the emotionally confronting aspect of the human cadaveric experience (Horne et al, ; Hancock et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, our repeaters often say openly that they feel pressure to pass the course with no further repetition for two reasons related to the regulations of our university: a more expensive repeater matriculation and the possibility of not being permitted to complete their engineering degree. The last reason is also present in the situation described by Schutte (2016) for repeaters. This could explain a more intense effort by these students and there is a clear need of making this issue the focus of further research as well.…”
Section: Level Of Homework Completion As Percentage Estimatesmentioning
confidence: 92%
“…Through discussions with numerous human anatomy instructors over the past decade, the authors have identified two commonly employed strategies for improving student success in undergraduate human anatomy. Some instructors attempt to identify study habits associated with successful knowledge retention and verbally guide poor performers toward more appropriate study practices (Schutte, ). Others choose to redesign their course structure using a wide variety of innovative anatomical teaching methods to bolster student engagement with course material (Berman, ).…”
Section: Introductionmentioning
confidence: 99%